Imagining the Rural Future: A Response to Howley, Clifton & Howley - Jason A. Cervone (Journal of Research in Rural Education, 2018)
I am pleased to be given the opportunity to respond to Howley, Clifton, and Howley's (2018) essay review of my book (Cervone, 2018) not only because the authors examine, critique, and expand on ideas beyond the viewpoint from which I wrote it, but also for the opportunity to revisit my own work and see what remains valid to me and where my own perspectives have changed. It has been a year since its publication and nearly two since the bulk of the work was completed. To say that much has changed politically in the United States in that time would be an understatement. To provide some context, this book began as my doctoral dissertation and was completed in the winter of 2016, with my defense coming three weeks after the election of Donald Trump. When the authors of the review refer to my critique as timely, it may be more apt than they know, as I was updating my drafts almost daily with each piece of legislation that Trump and Secretary of Education Betsy DeVos tried to push through.